Scorpion - Pryke, Louise M. (Animal (Reaktion Books), 2016)
From the back cover: "From the dawn of human civilization the scorpion has been a threatening figure in our imaginations--poisonous, precise and deadly quiet--but their bad reputation has overshadowed many exceptional qualities. Older than dinosaurs, these small arthropods have survived for hundreds of millions of years with very few changes to their form, and they have populated every continent--with the exception of Antarctica. Although humans and scorpions have coexisted for thousands of years, the image of the scorpion retains a sense of danger and mystery. Throughout our existence scorpions have served as powerful cultural and religious symbols--sometimes as menacing foes, other times as protectors. From the Egyptian goddess Serket to Zodiac astrology to folk medicine, Scorpion is a fascinating tour that includes ancient warrior deities, the American Civil War and the markets of Southeast Asia. Scorpion is a richly illustrated homage to one of earth's oldest residents."